Alexander Hamilton : ambivalent Anglophile - Kaplan, Lawrence S. (Wilmington, Del. : SR Books, 2002)
Of all of the Founding Fathers of the American republic none, with the possible exception of Thomas Jefferson, has evoked more passions and aroused more controversy than Alexander Hamilton. In this absorbing new biography, eminent historian Lawrence Kaplan examines Hamilton's conception of America's role in the world and the foreign policies that followed from his vision. Kaplan looks at how Hamilton acted upon his views in shaping the course of American foreign relations. The author provides a focused, accessible biography of Hamilton and a nuanced assessment of his impact on Federalist.
1. The Rise of a Wunderkind -- 2. The War as Opportunity, 1775-1782 -- 3. Toward the Constitution, 1782-1789 -- 4. Secretary of the Treasury, 1789-1791 -- 5. To the Jay Treaty, 1790-1794 -- 6. Behind the Scenes, 1795-1798 -- 7. General Manque, 1798-1800 -- 8. Epilogue.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Hamilton, Alexander, -- 1757-1804.; Hamilton, Alexander, -- 1757-1804.; Hamilton, Alexander, -- (1757-1804); Hamilton, Alexander -- Politiker; Statesmen -- United States -- Biography; United States -- Foreign relations -- 1775-1783.; United States -- Foreign relations -- 1783-1815.; United States -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- United States; Diplomatic relations; Statesmen; Great Britain; United States; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- United States -- State & Local -- General; Buitenlandse politiek; Außenpolitik; USA; 1775-1815; Electronic books; Biographies